Cross-Cultural Supervision in Cognitive-Behavioral Therapy: A Case Study. Issue 3 (August 2018) - Yang, Fa-Hui; Dobson, Keith; Li, Xiao-Miao; Hennebury, Adam; Gao, Ying; Tang, Xin-Feng; Qi, Le
Abstract: This article provides a thorough description of a representative case of online cross-cultural supervision by interviewing all parties involved in the supervision (the supervisor, the supervisee, and the translator). This study provides evidence about the benefits and challenges of online cross-cultural supervision and the feasibility of such a training modality. A cross-cultural supervision competence model and culturally adapted treatment stage model are proposed, and the article provides suggestions for future supervisors, supervisees, and translators. Highlights: This article describes a representative case of online cross-cultural supervision. This study discusses the benefits and challenges of online cross-cultural supervision and its feasibility. A culturally adapted competence and treatment stage model are proposed. Suggestions are provided for future supervisors, supervisees, and translators.